Processing effects on the antioxidant and total phenolic contents of jute leaves. - Hurtada, W. A.; Marciano, V.; Rodriguez, F. M. (2003)
The effect of the length of exposure (0, 5, 10 and 15 mins) of jute of saluyot leaves containing varying amount of salts (0, 2, 4 and 6g/L of water) at different temperature (room temperature (25°C), 50 °C, 75°C and 100 °C) on the total antioxidant activity and total phenolic content were investigated and were measured spectrophotometrically using the Modified Ferric Thiocyanate Method and the Folin-Ciocalteau Micromethod, respectively. Specific antioxidant compound were identified using High Performance Liquid Chromatography (HPLC). The identified antioxidant compounds in jute leaves were gallic acid, vanilic acid, ferlic acid, luteolin, quercetin, daidzein, and genistein. Vanilic and gallic acid concentrations were the highest among the identified compounds. Room temperature had significantly the highest total antioxidant activity, total phenolic content and concentration and time of exposure had significantly decreased the antioxidant compounds. However, there was significantly higher total antioxidant activity and total phenolic content at 100°C compared to 75°C. Combined treatments of heat, salt and time of exposure on the total antioxidant activity, total phenolic content and concentration levels of the identified antioxidant compounds present in jute leaves were also studied. This study showed that the effect of time and salt were temperature dependent. No definite trend can be derived from the effect of different salt concentrations with an increased temperature and time of exposure on the total antioxidant activity and total phenolic content. The total antioxidant activity and the total phenolic content of jute leaves had a positive moderate linear correlation. Vanillic acid, guercetin and luteolin were moderately correlated with both the total antioxidant activity and total phenolic content, whereas genistin and daidzein were moderately correlated with the total phenolic content.
Keywords: Saluyot (Vegetable); Leaves